2011
DOI: 10.5713/ajas.2011.10419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Soybean Meal on Immune Response of Weaned Calves with Experimentally Induced Lipopolysaccharide Challenge

Abstract: The present study was conducted to evaluate the effects of fermented soybean meal (FSBM) on the level of cortisol hormone and immune-related serum proteins in weaned calves after experimentally induced lipopolysaccharide (LPS) challenge. Holstein neonatal calves (n = 21; 8 males and 13 females, BW = 42.2±6.15 kg) were randomly allocated to one of two dietary treatments: SBM (control calf starter having soybean meal (SBM) as a main protein source) and FSBM (substitute SBM in control diet with FSBM) groups. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The beneficial effects of feeding FSBM based diets to a variety of ruminants as well as non-ruminants, both young and adult, have also been investigated and established (Mathivanan et al, 2006; Song et al, 2008; Yuan et al, 2012). Increase in the majority of growth promoting factors as well as health parameters are seen in farm and poultry animals (Feng et al, 2007a, b; Liu et al, 2007; Kwon et al, 2011). FSBM based diet is also recommended for certain fish species as a replacement of fish meal in several studies (Yamamoto et al, 2010; Kader et al, 2012; Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of feeding FSBM based diets to a variety of ruminants as well as non-ruminants, both young and adult, have also been investigated and established (Mathivanan et al, 2006; Song et al, 2008; Yuan et al, 2012). Increase in the majority of growth promoting factors as well as health parameters are seen in farm and poultry animals (Feng et al, 2007a, b; Liu et al, 2007; Kwon et al, 2011). FSBM based diet is also recommended for certain fish species as a replacement of fish meal in several studies (Yamamoto et al, 2010; Kader et al, 2012; Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there was a significant decrease (P<0.01) in blood, glucose, AST and ALT concentration with increasing digestamin levels. Kwon et al (2011) showed that, total serum Ig A and IgM levels significantly increased in both FSBM groups compared to un supplemented one. It could be suggest that, FSBM may have lower concentrations of allergenic and anti nutritional factors than the soybean meal which improve kidney and liver function of experimental animals (Wolfswinke, 2009).…”
Section: Blood Parametersmentioning
confidence: 81%
“…From an animal nutrition point of view, it has been suggested that feeding of peptides or fermented or enzymatically hydrolysed protein feedstuffs improved growth performance, is an effective way of meeting amino acid requirements in low‐protein diets and influences endogenous amino acid loses . Aside from nutritional effects, though, peptides also serve functional food roles and help to enhance gut health or reduce stress response . However, there is a scarcity of reports on the supplementation of peptides in poultry diets.…”
Section: Discussionmentioning
confidence: 99%